Implementation of Problem-Based Learning at SMAN 1 Gerung: A Reflection on Student Teaching Practice - Qothrunnada, Qothrunnada; Nisrina, Nina; Krisnawati, Kd. Yayuk (Indonesian Publication Center, 2024)
The PPL program at SMAN 1 Gerung was initiated to address the gap between the intended active, problem-based physics learning and the predominantly procedural classroom practices observed in the teaching of magnetic fields and the Lorentz force. This activity focused on employing a collaborative participatory action approach to strengthen students’ ability to observe phenomena, identify problems, and construct evidence-based arguments. The program consisted of three key stages: initial observation to map instructional needs, collaborative planning and enactment of problem-based lessons supported by phenomenon-driven demonstrations, and reflective discussions with teachers and students to evaluate the effectiveness of the implemented strategies. The results indicate increased student engagement, improved conceptual analysis, and stronger connections between theoretical principles and real-world contexts. The final reflection highlights that the collaborative participatory action framework enriched the instructional process and offers strong potential for future development, especially in advancing inquiry-based practices and scientific literacy in physics classrooms.